Monteggia lesion and its equivalents in children - Čepelík, M; Pešl, T; Hendrych, J; Havránek, P (Journal of children's orthopaedics, 2019)
Purpose: The aim of the study is to evaluate our group of paediatric patients with Monteggia lesion and its equivalents and to compare the characteristics of basic types of these lesions concerning therapeutic approach and results of the treatment. Methods: Retrospective study of 111 children treated in the Department of Pediatric and Trauma Surgery of the Thomayer Hospital in Prague between 2001 and 2013 (13 years). When evaluating the outcome of the therapy, Bruce's criteria modified by Letts that assesses range of movement, pain and deformity of the elbow joint were applied. Regarding the therapeutic approach, four groups were compared: nonoperative treatment, reduction and casting, closed reduction and internal fixation (CRIF) and opened reduction and internal fixation (ORIF). Results were compared between three groups of patients (Monteggia lesions, displaced equivalents and non-displaced equivalents) using Fisher´s exact test with α set to 0.05. Results: In all, 46 patients were treated for (true) Monteggia lesion, 27 for non-displaced Monteggia equivalent and 38 for displaced equivalent. There is a statistically significant difference in therapeutic approach between all three groups of patients. There is no significant difference in outcome between Monteggia lesions and both types of Monteggia equivalents, but there is a statistically significant difference between displaced and non-displaced equivalents. Conclusion: There are only two lesions that meet the criteria of Monteggia - (true) Monteggia lesion and displaced Monteggia equivalent. The non-displaced equivalent does not meet the criteria of Monteggia and, therefore, should not be termed a Monteggia equivalent. Level of Evidence: Level III - Retrospective comparative study.